In Vitro Studies of Pegylated Magnetite Nanoparticles in a Cellular Model of Viral Oncogenesis: Initial Studies to Evaluate Their Potential as a Future Theranostic Tool - Gabriel Principe; Virginia Lezcano; Silvina Tiburzi; Alicia B. Miravalles; Paula S. Rivero; María G. Montiel Schneider; Verónica Lassalle; Verónica González-Pardo (MDPI AG, 2023)
Magnetic nanosystems represent promising alternatives to the traditional diagnostic and treatment procedures available for different pathologies. In this work, a series of biological tests are proposed, aiming to validate a magnetic nanoplatform for Kaposi's sarcoma treatment. The selected nanosystems were polyethylene glycol-coated iron oxide nanoparticles (MAG.PEG), which were prepared by the hydrothermal method. Physicochemical characterization was performed to verify their suitable physicochemical properties to be administered in vivo. Exhaustive biological assays were conducted, aiming to validate this platform in a specific biomedical field related to viral oncogenesis diseases. As a first step, the MAG.PEG cytotoxicity was evaluated in a cellular model of Kaposi's sarcoma. By phase contrast microscopy, it was found that cell morphology remained unchanged regardless of the nanoparticles' concentration (1-150 µg mL−1). The results, arising from the crystal violet technique, revealed that the proliferation was also unaffected. In addition, cell viability analysis by MTS and neutral red assays revealed a significant increase in metabolic and lysosomal activity at high concentrations of MAG.PEG (100-150 µg mL−1). Moreover, an increase in ROS levels was observed at the highest concentration of MAG.PEG. Second, the iron quantification assays performed by Prussian blue staining showed that MAG.PEG cellular accumulation is dose dependent. Furthermore, the presence of vesicles containing MAG.PEG inside the cells was confirmed by TEM. Finally, the MAG.PEG steering was achieved using a static magnetic field generated by a moderate power magnet. In conclusion, MAG.PEG at a moderate concentration would be a suitable drug carrier for Kaposi's sarcoma treatment, avoiding adverse effects on normal tissues. The data included in this contribution appear as the first stage in proposing this platform as a suitable future theranostic to improve Kaposi's sarcoma therapy.